Method for synergistically optimizing carbon nano spiral aerogel through carbon layer / zinc oxide, obtained product and application

By depositing ZnO layer on the surface of carbon nanospiral aerogel and converting it into ZIF-8, then calcining to form a carbon layer, C/ZnO@CNC aerogel composite material is prepared, and the absorption bandwidth and coating of existing electromagnetic wave absorbing materials are solved. The lack of layer thickness, additive density, cost and durability in extreme environments achieves excellent electromagnetic wave absorption and photothermal conversion performance.

CN119390048APending Publication Date: 2025-02-07NANTONG QIANJIUXING TECHNOLOGY NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411507192.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing electromagnetic wave absorbing materials have shortcomings in absorption bandwidth, coating thickness, additive density, cost and durability in extreme environments, and are difficult to meet the demand for wide-frequency electromagnetic wave absorbers in civil and military fields.

Method used

By depositing a ZnO layer on the surface of a carbon nanospiral aerogel and soaking in dimethylimidazole methanol solution, the ZnO part is converted into ZIF-8 in situ, and then calcining under an inert atmosphere to convert ZIF-8 into a carbon layer, the preparation Out of C/ZnO@CNC aerogel composite material.

Benefits of technology

The C/ZnO@CNC aerogel composite material prepared by this method has excellent electromagnetic wave absorption and photothermal conversion performance, stable structure and strong thermal stability. It is suitable for electromagnetic wave absorption and photothermal conversion fields, and overcomes pure CNC gas Gels are underused in these fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390048A_ABST
    Figure CN119390048A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synergistically optimizing carbon nano spiral aerogel through a carbon layer / zinc oxide and an obtained product and application of the carbon nano spiral aerogel. Firstly, zinc oxide is deposited on the surface of CNC aerogel through an atomic layer deposition method, and ZnO-coated CNC aerogel is obtained; then, the ZnO (at) CNC aerogel is soaked in a dimethyl imidazole methanol solution, and the ZIF-8 / ZnO (at) CNC aerogel is obtained. Finally, the ZIF-8 / ZnO (at) CNC aerogel is roasted in an inert environment, and the C / ZnO (at) CNC aerogel composite material is generated. The C / ZnO-coated CNC aerogel composite material is prepared through atomic layer deposition, an impregnation method and a chemical vapor deposition method, the process is simple, the amount of ZnO can be accurately controlled, and the composite material has good conductivity, electromagnetic wave absorption performance and photothermal conversion performance and has wide application value in the fields of photothermal conversion, electromagnetic wave absorption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for carbon layer / zinc oxide synergistically optimizing carbon nano spiral aerogel, and also relates to a product obtained according to the method and application of the product in the field of electromagnetic wave absorption and photothermal conversion, belonging to the technical field of nano material preparation and application. Background Art

[0002] Electromagnetic wave absorbing materials that can eliminate electromagnetic radiation pollution generated by the widespread use of wireless electronic devices are gaining more and more attention. Therefore, extensive research on electromagnetic wave absorbing materials has also enhanced our understanding of the inherent mechanism of microwave loss. Based on these studies, a variety of electromagnetic wave absorbing materials with good performance have been developed, which can be divided into dielectric loss materials, magnetic loss materials, chiral materials and metamaterials.

[0003] However, many of these studies have focused too much on strong absorption capabilities and ignored other important properties, such as absorption bandwidth, coating thickness, or density of additives. In addition, in the face of the growing demand for electromagnetic wave absorbing materials in the civilian and military fields, material cost is also a key factor that must be considered. In addition to specific absorption properties, whether the material can be durable in extreme environments is also a crucial issue. Long-term use in extreme environments can easily lead to the failure of the material's electromagnetic wave absorption performance. Therefore, there is an urgent need to explore wide-frequency electromagnetic wave absorbers that are reasonably priced, have thin coating thickness, good stability, and can work in extreme environments.

[0004] Pure carbon nanocoil (CNC) aerogel is rarely taken seriously as an electromagnetic wave absorption or photothermal conversion material due to its generally high dielectric constant and poor photothermal conversion performance in the ultraviolet region. Therefore, in order to better use CNC aerogel in the field of electromagnetic wave absorption or photothermal conversion, it is of great significance to develop a CNC aerogel-based composite material with high electromagnetic wave absorption performance, good photothermal performance and environmental reliability through reasonable structural design and component optimization. Summary of the invention

[0005] In view of the shortcomings of CNC aerogel in electromagnetic wave absorption, photothermal conversion and other aspects, the present invention provides a method for carbon layer / zinc oxide synergistic optimization of carbon nano helical aerogel and the resulting product. The method has a simple process, and the structure of carbon nano helical (CNC) aerogel is optimized by carbon layer and zinc oxide. The resulting composite material has a stable structure, good electromagnetic wave absorption performance and photothermal conversion performance, and has wide application value in the fields of photothermal conversion, electromagnetic wave absorption and the like.

[0006] The specific technical solutions of the present invention are as follows:

[0007] A method for carbon layer / zinc oxide synergistic optimization of carbon nano helical aerogels, comprising the following steps:

[0008] (1) Depositing a ZnO layer on the surface of carbon nanotube (CNC) aerogel by atomic layer deposition to obtain ZnO@CNC aerogel;

[0009] (2) The ZnO@CNC aerogel was immersed in a dimethylimidazole methanol solution to convert the ZnO part into ZIF-8 in situ, thereby obtaining ZIF-8 / ZnO@CNC aerogel;

[0010] (3) The ZIF-8 / ZnO@CNC aerogel is calcined under an inert atmosphere to convert the ZIF-8 into a carbon layer to obtain a C / ZnO@CNC aerogel composite material.

[0011] Furthermore, the CNC aerogel used in the present invention can be prepared by a method disclosed in the prior art. For example, copper tartrate powder can be calcined at 220-280° C. in an acetylene environment for 1-2 hours, and then calcined at 800-850° C. in an inert environment for 1-2 hours to obtain CNC aerogel. The inert environment can be an inert atmosphere environment such as nitrogen and argon.

[0012] Furthermore, in step (1), the CNC aerogel is placed in an atomic layer deposition device for atomic layer deposition, so that a zinc oxide layer is deposited on its surface. The method of atomic layer deposition of ZnO can be carried out with reference to the method disclosed in the prior art.

[0013] In a specific embodiment of the present invention, the precursors of the atomic layer deposition are diethyl zinc and water, respectively, the deposition temperature is 140-160°C, and the deposition cycle is 100-400 cycles. The thickness of ZnO deposited on the surface of the CNC aerogel is controlled by adjusting the deposition cycle. Experiments show that the thickness of zinc oxide has a great influence on the morphology and performance of the final product, and is the key to the formation of the composition and morphology of the final product. Preferably, the deposition cycle is 200 cycles.

[0014] Further, in step (2), the ZnO@CNC aerogel composite material is impregnated in a dimethyl imidazole methanol solution by an impregnation method to form a ZIF-8 / ZnO@CNC aerogel composite material, and the impregnation can be performed in a glass container such as a beaker. The specific method of the impregnation method can refer to the method disclosed in the prior art, wherein the impregnation temperature has no special requirements and can be performed at room temperature or room temperature, for example, a temperature range of 20-30°C can be selected, and the impregnation time is 12-15h.

[0015] Furthermore, in step (2), the concentration of the dimethylimidazole methanol solution is 90-100 mmol / L.

[0016] Further, in step (3), the ZIF-8 / ZnO@CNC aerogel composite material is calcined in an inert environment by chemical vapor deposition to form a final C / ZnO@CNC aerogel composite material, and the calcination can be carried out in a tubular furnace. The specific method of the chemical vapor deposition method can refer to the method disclosed in the prior art, wherein the calcination temperature is preferably 450-500°C and the calcination time is 1-2h.

[0017] Furthermore, in step (3), the inert environment can be provided by an inert gas such as nitrogen or argon. During the calcination process, the inert gas is introduced at a rate of 45-55 mL / min.

[0018] The present invention first deposits a certain thickness of ZnO on the surface of CNC aerogel by atomic layer deposition, then adopts an impregnation method, and finally uses a chemical vapor deposition method to obtain a C / ZnO@CNC aerogel composite material with special morphology and excellent performance. The ZnO@CNC aerogel is immersed in a dimethyl imidazole methanol solution, and the ZnO part on the surface is converted into a ZIF-8 film in situ during the impregnation process. During chemical vapor deposition, the ZIF-8 / ZnO@CNC aerogel composite material is placed in an inert gas for calcination, and the ZIF-8 film is gradually converted into an amorphous carbon layer during the calcination process, and the entire product presents a layered nano-helical fiber structure at the microscopic level. In the composite material, carbon / ZnO is uniformly coated on the surface of the CNC aerogel, and the content of ZIF-8 and zinc oxide can be accurately controlled by controlling the reaction conditions.

[0019] The C / ZnO@CNC aerogel composite material obtained by the present invention is a layered nano-helical fiber structure in which a ZnO layer is coated on the surface of a CNC aerogel, and a carbon layer is coated on the surface of the ZnO layer. The composite material has excellent electromagnetic wave absorption performance and photothermal conversion performance, and has a stable structure and strong thermal stability. It can be used as an electromagnetic wave absorption material and a photothermal conversion material, and has good application prospects in the fields of electromagnetic wave absorption and photothermal conversion, overcoming the shortcomings of pure CNC aerogel in these fields. Therefore, the C / ZnO@CNC aerogel composite material prepared by the present invention and its application in the fields of electromagnetic wave absorption and photothermal conversion are also within the protection scope of the present invention.

[0020] The present invention uses CNC aerogel as the skeleton, and prepares C / ZnO@CNC aerogel composite material by atomic layer deposition, impregnation method and chemical vapor deposition method. Carbon / ZnO is uniformly coated on the carbon nano spiral aerogel, which greatly improves the electromagnetic wave absorption and light-heat conversion performance of CNC aerogel. Compared with the prior art, the advantages of the present invention are:

[0021] (1) The present invention combines atomic layer deposition technology, impregnation method and chemical vapor deposition to prepare C / ZnO@CNC aerogel composite, and the preparation process is simple and easy;

[0022] (2) The present invention prepares C / ZnO@CNC aerogel composite materials, and the thickness of ZnO can be precisely controlled by using the single-atom thin film growth technology of ALD, and the aerogel composite materials have a large specific surface area, many active sites, and excellent performance;

[0023] (3) The C / ZnO@CNC aerogel composite material prepared by the present invention has a stable structure. Experiments have shown that its performance is significantly improved compared with that of pure CNC aerogel. Due to its stable structure, the carbon material acts as a photothermal conversion agent, and ZnO increases its photothermal conversion performance in the ultraviolet region. It has broad application prospects in photothermal conversion.

[0024] (4) The C / ZnO@CNC aerogel composite material prepared by the present invention has excellent electromagnetic wave absorption performance and has broad application prospects in electromagnetic wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 SEM and TEM images of the samples of the present invention, (a) SEM image of CNC aerogel, (b) TEM image of ZnO@CNC aerogel, (c) TEM image of ZIF-8 / ZnO@CNC aerogel, (d) TEM image of C / ZnO@CNC-1 aerogel, (e) TEM image of C / ZnO@CNC-2 aerogel, (f) TEM image of C / ZnO@CNC-3 aerogel.

[0026] Figure 2 XRD patterns of C / ZnO@CNC-1, C / ZnO@CNC-2 and C / ZnO@CNC-3 aerogels.

[0027] Figure 3 Electromagnetic parameter diagram of CNC aerogel.

[0028] Figure 4 This is the electromagnetic parameter diagram of C / ZnO@CNC-1 aerogel.

[0029] Figure 5 This is the electromagnetic parameter diagram of C / ZnO@CNC-2 aerogel.

[0030] Figure 6 This is the electromagnetic parameter diagram of C / ZnO@CNC-3 aerogel.

[0031] Figure 7 This is a diagram showing the electromagnetic wave absorption performance of CNC aerogel.

[0032] Figure 8 This is the electromagnetic wave absorption performance diagram of C / ZnO@CNC-1 aerogel.

[0033] Fig. 9This is the electromagnetic wave absorption performance diagram of C / ZnO@CNC-2 aerogel.

[0034] Fig.10 This is the electromagnetic wave absorption performance diagram of C / ZnO@CNC-3 aerogel.

[0035] Fig.11 This is the photothermal conversion performance diagram of C / ZnO@CNC-3 aerogel.

[0036] Fig.12 For C / ZnO@CNC-3 aerogel at 300 mW cm -2 Long-term irradiation temperature and infrared photos under different light intensities. DETAILED DESCRIPTION

[0037] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary implementation modes are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.

[0038] Example 1 Preparation of C / ZnO@CNC aerogel composite material

[0039] (1) Synthesis of CNC aerogel by chemical vapor deposition

[0040] The copper tartrate powder was placed in a porcelain boat, calcined at 250°C for 1 hour in an acetylene environment, and then calcined at 800°C for 2 hours in an argon environment to obtain CNC aerogel.

[0041] (2) Preparation of ZnO@CNC aerogel by atomic layer deposition

[0042] The CNC aerogel was placed in an atomic layer deposition device to deposit ZnO using the atomic layer deposition method. During the atomic layer deposition, diethyl zinc and water were used as precursors, the deposition temperature was 150°C, and the deposition was repeated for 200 cycles to obtain a ZnO@CNC aerogel composite material.

[0043] (3) Preparation of ZIF-8 / ZnO@CNC aerogel composites by impregnation method

[0044] The ZnO@CNC aerogel was immersed in a 96 mmol / L dimethylimidazole methanol solution by the immersion method at 25°C for 12 hours. During the immersion process, the ZnO on the surface was partially converted into a ZIF-8 film in situ.

[0045] (4) Preparation of C / ZnO@CNC aerogel composites by annealing method

[0046] During annealing, the ZIF-8 / ZnO@CNC aerogel composite material was placed in a tubular furnace and calcined by introducing argon gas. The introduction rate of argon gas was 50 mL / min, the calcination temperatures were 350°C, 400°C and 450°C, and the calcination time was 2 hours. The obtained products were named C / ZnO@CNC-1, C / ZnO@CNC-2 and C / ZnO@CNC-3 aerogel composite materials.

[0047] During the calcination process, the ZIF-8 film gradually transforms into an amorphous carbon layer, and the entire product presents a layered nano-helical fiber structure at the microscopic level. In this composite material, carbon / ZnO is evenly coated on the surface of the CNC aerogel, and the content of ZIF-8 and zinc oxide can be precisely controlled by controlling the reaction conditions.

[0048] Figure 1 The electron microscope image of the obtained C / ZnO@CNC shows the process of forming a layered nano-helical fiber structure with a surface-coated carbon layer. The skeleton fiber diameter of the CNC aerogel is 140-160nm. The thickness of ZnO after 200 cycles of deposition is 22nm. The ZnO@CNC aerogel composite material forms a ZIF-8 film after impregnation. Figure 2 The XRD graph of the C / ZnO@CNC aerogel shown in the figure shows that as the calcination temperature increases, ZIF-8 gradually transforms into a carbon layer, the diffraction peak of ZIF-8 gradually weakens, and is evenly coated on the surface of ZnO@CNC. When the calcination temperature reaches 450°C, ZIF-8 is completely transformed into a carbon layer, the diffraction peak of ZIF-8 completely disappears, and the surface is loaded with ZnO nanoparticles. This structural transformation is the key to improving the absorption performance.

[0049] Application Example 1

[0050] Application of composite materials in electromagnetic wave absorption:

[0051] (1) Add sample and paraffin in a beaker at a mass ratio of 15:85.

[0052] (2) Place the beaker on a 60°C hot plate to mix the sample and paraffin evenly.

[0053] (3) The uniformly mixed sample and paraffin are placed in a mold to prepare a ring with an inner diameter of 3.04 mm, an outer diameter of 7.00 mm, and a thickness of 2.00 mm.

[0054] (4) Each ring is placed on a vector grid analyzer and the electromagnetic parameters are measured at different frequencies. The results are as follows Figure 3-6 shown.

[0055] It can be seen from the figure that the dielectric real part ε' and dielectric imaginary part ε" values ​​of CNC aerogel show frequency dispersion characteristics in the entire frequency range. The dielectric real part ε' of CNC aerogel decreases from 15.78 to 5.50, and the dielectric imaginary part ε" decreases from 7.19 to 3.57. The dielectric real part ε' of C / ZnO@CNC aerogel shows frequency dispersion characteristics, while the dielectric imaginary part ε" fluctuates in the entire frequency range. The dielectric real part ε' of C / ZnO@CNC-1 aerogel decreases from 10.06 to 6.54, and the dielectric imaginary part ε" fluctuates between 2.22 and 3.49. The real part of the dielectric ε' of C / ZnO@CNC-2 aerogel decreased from 11.83 to 7.20, and the imaginary part of the dielectric ε" fluctuated between 2.72 and 3.82. The real part of the dielectric ε' of C / ZnO@CNC-3 aerogel decreased from 11.52 to 5.25, and the imaginary part of the dielectric ε" fluctuated between 2.82 and 3.87. The changes in the ε' and ε" values ​​of C / ZnO@CNC aerogel are very similar. The electromagnetic wave absorption performance is high, which is mainly due to two key factors: good impedance matching ability and dissipation ability. The carbon layer and ZnO layer with suitable structure can produce good impedance matching with the free space. The void space in the C / ZnO@CNC aerogel structure will cause multiple reflections and scattering, which is very effective in improving the absorption of electromagnetic waves. The real and imaginary parts of the complex magnetic permeability are approximately 1 and 0, respectively, which is consistent with the fact that the sample does not contain magnetic components.

[0056] The electromagnetic wave absorption performance of each sample is as follows Figure 7-10 As shown in the figure, it can be seen that the electromagnetic wave absorption performance of CNC aerogel is poor. With the increase of calcination temperature, the electromagnetic wave absorption performance of C / ZnO@CNC gradually improves, and the electromagnetic wave absorption performance of C / ZnO@CNC-3 is the best.

[0057] Application Example 2

[0058] Application of composite materials in the field of photothermal conversion:

[0059] (1) Polytetrafluoroethylene was selected as the polymer, and the C / ZnO@CNC-3 aerogel composite material and commercially available polytetrafluoroethylene emulsion (solid content 60 wt%) were weighed and added into a beaker in a mass ratio of 15:142. Then, an appropriate amount of ethanol was added to break the emulsion and stirred evenly until it was formed.

[0060] (2) Place each sample on a glass plate, adjust the position of the xenon lamp so that the center of the xenon lamp is aimed at the sample, and then adjust the light intensity to irradiate the sample. After irradiation for 3 minutes, turn off the light source and let it cool naturally for 5 minutes. During the entire experiment, use an infrared camera to record the temperature change of the sample every 10 seconds. The results are as follows: Fig.11 As shown in the figure, at 300mWcm -2Under different light intensities, the temperature of the mixture of C / ZnO@CNC-3 aerogel and PTFE can reach 77.4°C. Under different light intensities, the time it takes for the sample to reach the highest temperature is basically the same, and the cooling time of the sample is also basically the same.

[0061] (3) Use a xenon lamp to adjust 300mW cm -2 The sample was irradiated with a light intensity of , and the light source was turned off after 1100 seconds, and the sample was cooled naturally for 5 minutes. Fig.12 As shown in the figure, under long-term irradiation, the surface temperature of the C / ZnO@CNC-3 aerogel and PTFE mixture remains basically unchanged, showing good thermal stability.

Claims

1. A method for synergistically optimizing carbon nano-helical aerogels by carbon layer / zinc oxide, characterized in that The following steps are involved: (1) Depositing a ZnO layer on the surface of carbon nanohelical aerogel by atomic layer deposition to obtain ZnO@CNC aerogel; (2) The ZnO@CNC aerogel was immersed in a dimethylimidazole methanol solution to convert the ZnO part into ZIF-8 in situ, thereby obtaining ZIF-8 / ZnO@CNC aerogel; (3) The ZIF-8 / ZnO@CNC aerogel is calcined under an inert atmosphere to convert the ZIF-8 into a carbon layer to obtain a C / ZnO@CNC aerogel composite material.

2. The method according to claim 1, characterized in that: In step (1), during atomic layer deposition, the precursors are diethyl zinc and water, the deposition temperature is 140-160° C., and the deposition cycle is 100-400 cycles.

3. The method according to claim 1 or 2, characterized in that: The preparation method of the carbon nano spiral aerogel is as follows: the copper tartrate powder is calcined at 220-280°C in an acetylene environment for 1-2 hours, and then calcined at 800-850°C in an inert environment for 1-2 hours to obtain the carbon nano spiral aerogel.

4. The method according to claim 1, characterized in that: In step (2), the concentration of the dimethylimidazole methanol solution is 90-100 mmol / L.

5. The method according to claim 1 or 4, characterized in that: In step (2), the soaking time is 12-15 hours.

6. The method according to claim 1, characterized in that: In step (3), the calcination temperature is 450-500° C. and the calcination time is 1-2 h.

7. A C / ZnO@CNC aerogel composite material, characterized by: The carbon nano-helical aerogel is prepared by the method for synergistically optimizing carbon layer / zinc oxide according to any one of claims 1 to 6.

8. The C / ZnO@CNC aerogel composite material according to claim 7, characterized in that: In the C / ZnO@CNC aerogel composite material, the surface of the CNC aerogel is coated with a ZnO layer, and the surface of the ZnO layer is coated with a carbon layer.

9. Use of the C / ZnO@CNC aerogel composite material according to claim 7 or 8 in the field of electromagnetic wave absorption.

10. Application of the C / ZnO@CNC aerogel composite material according to claim 7 or 8 in the field of photothermal conversion.